La construcción de la memoria genealógica en Ennio (Annales, I) - Gaeta, Silvana Andrea (Cuadernos de Filología Clásica. Estudios Latinos, 2003)
Our aim o this paper to analyze how Ennio (239-169 WC.) in his Annals builds up an epic, not focused in a mythic character —like many other poems— but in the greatness of Roman spirit. Within this proposal, Book One has a leading role, since its very beginning. Ennius creates the «genealogical memory (Thomas), received as the foundation on which the Roman past, its identity and the forthcoming values will rest. Therefore, in the remaining fragments, our author narrates the confluence, o llia’s character and her sons, Romulus and Remu, of both family branches: The Latin —that goes back until Saturn— and the Trojan one —that, since Anquises and Venus, reaches AEneas—. The recurrence of vocabulary related to family ties, such as pater, nepos, genitor/genetrix. will be philologically studied. These terms constitute textually a mythical-historical framework, which constructs o a literary code the first great Roman genealogy. In this way the lines that Ennios suggests from the very beginning of his work found in a glorious past the genesis of the values the Romans will exalt along the Republic and the Empire.